Investigating the Implementation of Higher Order Thinking Skills in Malaysian Classrooms: Insights from L2 Teaching Practices (Sains Humanika, 2017)
In preparing for the 21st century workforce, many education systems have integrated creative and critical thinking elements in the teaching and learning process by instilling higher order thinking skills (HOTS) in students. This research examines English language (L2) teachersâ€™ awareness and practices in promoting HOTS in the English Language classrooms in Malaysia. Data were collected from practicing L2 teachers through questionnaires, semi-structured interviews and structured observations. Findings of this research suggest that implementation of HOTS in the L2 classroom is very minimal and hindered by various factors, particularly those related to student, pedagogical and institutional factors. This implies the need for a more holistic and integrated approach involving L2 teachers, students and administrators in ensuring the successful implementation of HOTS in the L2 classrooms.Â
Keywords: Higher order thinking skills; creative thinking; critical thinking; classroom practice